Financial Performance of Selected Regional Rural Banks in Jammu and Kashmir- An Empirical Study - Prof. Nisar Ahmed Mulla, Attaullah Niazi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Regional Rural Banks(RRBs) have been formed to serve rural areas with banking and other financial Services. These institutions were brought in the public domain through an ordinance passed by the then President of India in September 1975, with the intent of providing banking and credit facilities for the agriculture and other rural section of the society across the nation. They are key financing institutions at rural levels that provides agriculture credit in rural areas. RRBs have more access to rural areas and play a key role in strengthening the agriculture sector & rural development of India. The main objectives behind the formation of such type of vibrant institution in India was to established a link between the banks and rural households, especially in banking deprived areas. Moreover, to encourage rural savings, to generate employment opportunities, and to provide cheaper credit to the marginalised section in rural India. Presently, the RRBs are under great pressure and going towards financial distress (As revealed from studies). In this paper, an attempt has been made to study the financial performance of Selected Regional Rural banks (RRBs) of J&K by applying “CAMEL” Model approach. The finding of the study revealed that the performance of the J&K Grameen Bank(JKGB) and Ellaquai Dehati Bank(EDB) is not up to the mark.